Mecanismo em nuvem de monitoramento a dados sensíveis - Souza, Rafael Tomé de (Universidade Federal de São Carlos, 2014)
The privacy guarantee of a person s data is understood as the capacity of this person to manage, store, change, restrict or disclose for groups of individual of his choice. The data shared can be sensitive, revealing private content that deserves protection in sharing, for example financial personal information. In many computing services a lot of sensitive data does not have any mechanism that guarantees the owner s privacy. This work shows a mechanism that guarantees the privacy of the person who has the data accessed, the data owner, and the privacy of the person who accesses the data. It was developed a cloud monitoring mechanism for data whose access needs to be monitored with intrusion detection scenario available for the data owner. The propose feasibility was evaluated by response time test of a monitored page access, server overload and the server resource consumption through the prism of an application using the mechanism. Such mechanism has been a viable solution due to its minimal impact in computational resources and a solution that assists in sensitive data access monitoring.
Keywords: Sistemas distribuídos; Privacidade; Auditoria; Computação em nuvem; Auditing; Peudonym auditing; Privacy; Sensitive data; Cloud computing; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO